Phyto-Inhibitory and Antimicrobial Activity of Brown Propolis from Romania - Mihaela Laura Vică; Mirel Glevitzky; Ramona Cristina Heghedűş-Mîndru; Gabriela-Alina Dumitrel; Gabriel Heghedűş-Mîndru; Maria Popa; Doriana Maria Faur; Ștefana Bâlici; Cosmin Adrian Teodoru (MDPI AG, 2023)
The objective of this paper was to study the phyto-inhibitory and antimicrobial activity of brown propolis collected from the counties of four regions in Romania. The main physico-chemical and functional properties of 16 samples of propolis from different landforms of geographical regions were determined. Their antimicrobial activities were established against 5 bacterial strains (Pseudomonas fluorescens, Bacillus subtilis, Bacillus cereus, Escherichia coli, and Proteus mirabilis) and 5 fungal strains (Alternaria alternata, Cladosporium cladosporioides, Fusarium oxysporum, Mucor racemosus, and Aspergillus niger). Simultaneously, the phyto-inhibitory effect of propolis samples on different cereals was highlighted: hexaploid bread wheat (Triticum aestivum), maize (Zea mays L.), oats (Avena sativa L.), and barley (Hordeum vulgare L.). Correlations between the antioxidant activity and total flavonoid and phenol content of the propolis samples were identified, respectively, and the statistical analysis highlighted that the diameter of the inhibition zone was influenced by the strain type (bacterial and fungal) and the geographical regions of propolis. Principal component analysis (PCA) indicated that out of seven principal components, only two exhibited > 0.5. Pearson's correlation coefficient showed a low and moderate positive linear relationship between the diameter of the inhibition zone and the flavonoid and phenol concentration of the propolis samples.